Primary and stem cell transplantation for functional repair of striatal degeneration in Parkinson’s and Huntington’s disease - Lelos, Mariah J. (Henry Stewart Talks, 2013)
Neural transplantation of primary fetal tissue and stem cells, Parkinson’s and Huntington’s disease, Dopaminergic and medium spiny neurons, Results of clinical trials, Pre-clinical testing in rodent models of disease
Archived at 2022/01/31